The validity of the group personality projective test and its use in South African clinical psychology - Stonestreet, Gerald (Department of Psychology, 2016)
Following a discussion of the relationship between abnormal personality and psychopathology, and the concept of validity in psychometrics, the development and present form of the GPPT are described. Several important criticisms of the test are then detailed together with a review of all published research relating to it. Considering the HSRC's interest in standardising this instrument for use in South Africa, and since it is being extensively used for individual assessments within Stikland Hospital, four studies have been undertaken to clarify its validity: Study 1 concerns normative data and shows, from the test-results of 100 Afrikaans working adults of Bellville, that South African norms can be expected to differ radically from those obtained in the USA. Study 2 concerns the construct validity of the GPPT scales. Based on data from 168 Stikland patients, correlations between GPPT scores and a large number of other personality measures indicate that some of the interpretations offered by the test-developers are invalid for this population. Study 3 concerns the validity of the test as a measure of "mental health", and shows that, where significant, score deviations are related to neurotic rather than to sociopathic or psychotic maladjustment. Age and sex were not systematically related to score variance except for the "Withdrawal" scale, where a slight tendency was found for females to score higher. No single GPPT scale, including the composite "total score", was effective for reliable individual assessment of mental health. Study 4 concerns the test's validity as a measure of adjustment by investigating the scores before and after treatment of certain patients who improved dramatically. Results indicate that the TRQ and Total scores are effective in this respect.